A Bibliometric Analysis of Islamic Parenting Trend in Indonesia - Risa Nalwi Fatimah; Baharudin Baharudin; Wan Jamaluddin Z; Imam Syafe’i; Umi Hijriyah; Zahra Rahmatika; Mohamad Fauzan Adima (PT. Pusmedia Group Indonesia, 2024)
This study aims to analyze the development, trends, and identify the novelty of scholarly publications on Islamic Parenting in Muslim families in Indonesia from 2019 to 2024. The research method used is a Systematic Literature Review with Bibliometric Analysis data processing technique. A total of 33 articles from 220 indexed in Sinta 1 and Sinta 2 were included and visualized using VOSViewer 1.6.20. The results show that the highest number of publications occurred in 2022, with the most citations recorded in 2019. Of the 25 journals contributing to articles on Islamic Parenting, 64% employed qualitative methods. Based on the overlay visualization co-occurrence, research topics related to the “Sandwich Generation” and the “Digital Era” emerged as the most recent developments in the field.